2014
DOI: 10.1159/000358329
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Homozygous Mutation of the <b><i>IGFALS</i></b> Gene in a Female Adolescent: Indirect Evidence for a Contributing Role of the Circulating IGF-I Pool in the Pubertal Growth Spurt

Abstract: Background: Mutations of the IGFALS gene have been reported since 2004 in 24 patients, but only 5 of these are females. Case Report: We describe a 14.7-year-old female of a consanguineous Moroccan family with growth retardation and normal-onset but slow progression of puberty without manifest pubertal height gain. Results: At age 3.2 years, the patient's height was 85.5 cm (-2.9 SDS) and her weight 9.9 kg (-2.9 SDS) with a head circumference of 44.5 cm (-3.3 SDS). Serum IGF-I and IGFBP-3 concentrations were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…Two had a previously described homozygous IGFALS mutation c.401TOA (31,32), and one had a novel c.1291delT mutation. The individual with a novel mutation has been recently published as a case report (33). The novel mutation was a splice site, single-base deletion in exon 2, which was predicted to result in a frameshift leading to a premature stop codon and abolition of the leucine-rich repeats between amino acid residues 574-618, required for protein-protein interactions.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Two had a previously described homozygous IGFALS mutation c.401TOA (31,32), and one had a novel c.1291delT mutation. The individual with a novel mutation has been recently published as a case report (33). The novel mutation was a splice site, single-base deletion in exon 2, which was predicted to result in a frameshift leading to a premature stop codon and abolition of the leucine-rich repeats between amino acid residues 574-618, required for protein-protein interactions.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…From the original report in 2004, at least 30 patients with complete ACLSD have been characterized . In autosomal recessive genetic diseases, patients arise usually in consanguineous families being both parents’ carriers for the same pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have characterized ACLSD in four children presenting either short stature, normal stature but shorter than mid- From the original report in 2004, 1 at least 30 patients with complete ACLSD have been characterized. [3][4][5][6] In autosomal recessive genetic diseases, patients arise usually in consanguineous families being both parents' carriers for the same pathogenic variants. However, in ACLSD more than 40% of the patients reported were compound heterozygous for two different variants inherited from nonrelated parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of ALS gene mutations on simple heterozygosity, the International ALS Society conducted a study on family members of patients with ALS-D. They used data collected for 21 patients who were homozygotes or compound heterozygotes, and for 44 family members who were heterozygous carriers 36 or who lacked ALS gene mutations 8 . This study demonstrated a potential dose effect because homozygotes and compound heterozygotes were approximately 1.5 SDS shorter than heterozygous carriers, and, in turn, these were an average of 1 SDS shorter than individuals without mutations.…”
Section: Effect Of Mutation On Simple Heterozygositymentioning
confidence: 99%